Attitude of Midwives towards Fluoride Recommendations and Oral Prevention in Infants and Young Children - Antje Geiken; Louise Holtmann; Christof E. Doerfer; Christiane Schwarz; Christian Graetz (Children, 2022)
Early childhood caries is a challenge. Early dental screening flanked by multidisciplinary preventions by pediatricians, dentists, and midwives (MWs) may be helpful. New recommendations for dental screening in children (FUs) and fluoride have been introduced in Germany. The aim of this study was to investigate whether midwives consider FUs useful and implement early childhood caries prevention, as well as fluoride recommendations. The survey was conducted using an online questionnaire. Demographic data, including 11 items on early childhood dental prophylaxis and fluoride, were requested. Agreement was recorded using Likert scales. The data were analyzed descriptively. Two hundred and seventeen female MWs participated (age: 44.1 (11.04) years). One hundred and four (47.9%) participants knew about the FUs. Of the MWs, 30.7% found a referral from the first tooth to be very important (important/neutral/unimportant: 27%/27.9%/14.4%), compared with 84.8% for the entire primary dentition (11.8%/2.8%/0.5%). Of the MWs, 41.7% always recommended fluoride toothpaste from the first tooth (often/occasionally/rarely/never: 22.7%/12.4%/7.9%/15.3%) and 48.1% completely rejected fluoride-free toothpaste (always/often/occasionally/rarely: 9.8%/8.9%/17.3%/15.9%). In addition, 54.8% never recommended the use of fluoride tablets (always/often/occasionally/rarely: 9.2%/7.4%/10.2%/18.4%). The FUs are not yet well-known among MWs, and only less than one-third recommended dental check-ups, starting with the first tooth. This contrasts with the high uptake of fluoridated toothpaste. More educational work should be carried out to convince more MWs of the benefits of the FUs.